Physical exercise on the rat ventral prostate: Steroid hormone receptors, apoptosis and cell proliferation - Teixeira, G. R. [UNESP]; Favaro, W. J.; Pinheiro, P. F. F. [UNESP]; Chuffa, L. G. A. [UNESP]; Amorim, J. P. A. [UNESP]; Mendes, L. O. [UNESP]; Fioruci, B. A. [UNESP]; Oba, Eunice [UNESP]; Martins, O. A. [UNESP]; Martinez, M.; Martinez, Francisco Eduardo [UNESP] (Wiley-Blackwell, 2012)
Studies have investigated the effect of exercise on prostate cancer risk. However, there are still doubts regarding the correlation between physical activity and the steroid hormones with respect to the reduction of the risk for prostatic lesions. We evaluated the levels of corticosterone, dihydrotestosterone (DHT), testosterone, estradiol, and steroid hormone receptors, and investigated the relationship between apoptosis and cell proliferation in the rat ventral prostate after training. Two groups were included in this study: control and trained. The trained group was submitted to training for 13 weeks (1 week of adaptation). Two days after the last training session, all animals were euthanized, and the intermediate and distal regions of the ventral prostate were collected and processed for immunohistochemistry, Western blotting and hormonal analyses. Physical exercise increased the corticosterone plasma, DHT and testosterone. In addition, androgen receptor expression was lower and estrogen receptor (ER) a and ER beta expression were higher in the trained group. However, the trained group showed disruption of the ratio of apoptotic to proliferating cells, indicating a predominance of apoptosis. We conclude that physical exercise alters the sex hormones and their receptors and is associated with the disruption of the balance between apoptosis and cell proliferation in the rat ventral prostate.
Keywords: ventral prostate; physical exercise; hormones; apoptosis; cell proliferation